Long-term outcomes of percutaneous coronary intervention for unprotected left main coronary artery according to the synergy between percutaneous coronary intervention with taxus and cardiac surgery (SYNTAX) score. Issue 4 (June 2020) - Shiyovich, Arthur; Perl, Leor; Vaknin-Assa, Hana; Greenberg, Gabriel; Samara, Abed; Kornowski, Ran; Assali, Abid
Abstract : Background: Percutaneous coronary intervention (PCI) of unprotected left-main coronary artery (uLMCA) is increasingly performed. Although it is recommended to calculate the SYNTAX score, if uLMCA PCI is considered, data of outcomes by the SYNTAX score are scarce, particularly among patients with high score (SYNTAX ≥ 33). Objective: To evaluate long-term outcomes of uLMCA PCI according to SYNTAX score in real-world practice. Methods: Patients following PCI of uLMCA throughout 2006–2018, in a tertiary hospital, were included and classified into three groups according to the SYNTAX I score. The primary outcome was three-year major adverse cardiac event (MACE) comprising all-cause mortality, myocardial infarction (MI), target vessel revascularization (TVR), or coronary artery bypass surgery (CABG). Results: Overall 632 patients were analyzed, mean age 72.8 ± 11.5, males: 69%, classified as following: SYNTAX <22 ( n  = 225); SYNTAX 22–32 ( n  = 250) and SYNTAX ≥33 ( n  = 157). Patients with greater SYNTAX score had higher prevalence of diabetes mellitus, renal failure, peripheral arterial disease and stroke. Additionally, they had lower ejection fraction, greater EuroScore, and number of vessels involved. Procedural success rates were very high (>95%) and did not depend on the SYNTAX score. The rates of MACE and its components were significantly higher in patients with higher SYNTAX score. Multivariate analysis showed that SYNTAX score is an independent predictor of three-year MACE following uLMCA PCI [HRSYNTAX22-32  = 3 (95% confidence interval [CI]: 1.2–11.5), HRSYNTAX≥33  = 3.4 (95% CI: 1.8–13.3]. Conclusions: Despite the high success rates of uLMCA PCI in real-world patients with high SYNTAX score, the latter was significantly associated with worse three-year outcomes. Abstract : Supplemental Digital Content is available in the text.